Globalizzazione, disuguaglianze e nuovi approcci verso un modello di capitalismo sostenibile - Mirabelli, Maria; Fortunato, Vincenzo; Artiles, Antonio Martin (SocietàMutamentoPolitica, 2023)
The paper deals with a topic particularly relevant in the current international sociological debate such as the varieties of capitalisms and their evolutions. In particular, looking at the Italian experience, in a context of increasing uncertainty and inequalities, it focuses attention to the main socio-economic changes and their impact on economy and society, searching for a more equal, sustainable and inclusive model of capitalism. These changes induced the scholars to talk about a new “great transformation” by adopting the famous expression of Karl Polanyi, used to describe the birth of the market economy. Starting from the literature and available data, the paper suggests new possible paths as well as complementary or even alternative practices that keep together economy and society in order to start a new age of a more sustainable, social and inclusive capitalism. The central idea is that self-regulating markets do not perfectly work; their deficiencies, not only in their internal workings, but also in their consequences for less advantaged people, are so great that the state intervention becomes necessary and that the pace of change is of central importance in determining these consequences. We argue that a paradigm shift is urgently needed, but this will certainly take time and a new governance which requires the involvement of several key political, economic and social actors such as international organizations, national governments, economic organizations along with social movements and no-profit organisations embedded at national and local level.